A cohesive zone model for fracture initiation and propagation of fused silica direct bonding interface. (1st October 2019) - Maurel-Pantel, A.; Voisin, M.; Bui, Q.; Cocheteau, N.; Lebon, F.; Hochard, C.
Highlights: A phenomenological cohesive zone model for fracture of direct bonded assemblies. Tests performed to characterize fracture propagation and initiation on a free edge. Macroscopic CZM is atomistically motivated and identified on experiments. The finite elements model implemented has a good correlation with experiments. Abstract: Fused silica direct bonding is of particular interest for optical system manufacturing for spatial applications. However, in order to validate the European Space Agency standards, a better understanding of the assemblies mechanical behavior is required. Therefore, it is important to develop some predictive tools to determine numerically mechanical strength of complex assemblies. In this paper, a cohesive zone model is proposed to model the direct bonding interface behavior. In order to determine the mechanical strength of the interface, a propagation test, and an initiation test on a free edge the cleavage test have been performed on direct bonded fused silica samples. The FIT test (Flexible Initiation Test) is also used to identify the properties of the direct bonding joint. At the end, a comparative analyses is proposed between experimental results and finite elements models of the propagation and initiation tests.